Le radicalisme de Michael Moore - Jean-Marie Ruiz (Revue LISA)
Michael Moore is famous and popular in many European countries, where he is seen as a critic of American culture. However, his main thesis, which is repeatedly expressed in his films and books, does not primarily criticize American popular culture or political tradition. Rather, this article argues that Moore’s thought may best be analysed through the American tradition of radicalism, whose origin dates back to Thomas Paine. Obviously, Moore is a contemporary radical who uses the modern media to reach as many people as possible. Yet some aspects of his rationale are surprisingly close to 18th century American radicalism.